Cryptocurrency Operating Principle, Market and Risks - Pataki, Péter; Zörög, Zoltán (Acta Carolus Robertus, 2023)
Over the last decade or 1 - 1.5 years, financial markets have witnessed the mass emergence of virtual currencies based on blockchain technology, also known as cryptocurrencies. The most widely known is Bitcoin, the first representative, but today there are around 22,500 other cryptocurrencies. Many people see cryptocurrencies as an investment product with a high potential return, but are not aware of their operating mechanisms and the risks involved. There is a lively debate in financial circles on whether and to what extent crypto-currencies and their markets should be regulated. This paper will provide an overview of the characteristics of cryptocurrencies, their main types, possible directions for further development and the risks they entail, based mainly on international literature.